Smart Cities Social and Environmental Challenges and Opportunities for Local Authorities - Belaïd, Fateh; Arora, Anvita (Studies in Energy, Resource and Environmental Economics, 2024)
This edited volume discusses the socioeconomic, environmental, and policy implications of smart cities. Written by international experts in energy economics and policy, the chapters present wide range of high quality theoretical and empirical studies at the nexus of social, entrepreneurial, governmental and ecological transformation. The book covers a wide range of topics, with a view towards providing empirical evidence of the benefits of smart cities as well as practical frameworks for smart city initiatives. Topics discussed include: smart city transition pillars, innovation for smart and sustainable cities design and implementation, smart city governance, smart mobility within cities, and smart cities in emerging economies. This volume will be of use to students and researchers interested in resource economics, energy economics, sustainability, ICT, and governance, as well as policymakers working on smart city initiatives. This is an open access book.